Studi Tentang Etika Profesi dan Kode Etik Pustakawan - Puspitha, Dessy (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2022)
The librarian's Code of Ethics is a norm or rule that librarians must comply with to maintain honor, dignity, image, and professionalism. The code of ethics for Indonesian librarians is listed in the AD ART of the Indonesian Librarians. The 2006 Indonesian Librarian Code of Ethics states that the Indonesian librarian code of ethics serves as a guideline for the behavior and performance of all members of the Indonesian Librarian Association in carrying out their duties in the field of librarianship. Every member of the Indonesian Librarian Association has the responsibility to implement this code of ethics to the highest standards for the benefit of users, the profession, libraries, professional organizations, and society. The existence of a code of ethics in professional organizations shows that professional organizations are still stable. In the process of establishing a code of ethics, it can only be carried out by a professional organization that is valid and binding on its members. The establishment of a code of ethics is usually done at a congress of professional organizations. In the library, there are various types of work that are the responsibility of librarians. Even though there are differences between one and another, basically the goal is the same, namely to provide information services to users.